Risk assessment in fleet management system using OCTAVE allegro - Salman Alfarisi; Nico Surantha (Institute of Advanced Engineering and Science, 2022)
The purpose of this study is to use the OCTAVE allegro methodology to identify risks in fleet management system (FMS), determine prioritized risks to be mitigated, provide mitigation recommendations for these prioritized risks, and shows how effective the recommendation is. The result of this study is expected to become an input for FMS service provider of possible risks in FMS services, and risk mitigation approaches that can be used to handle those risks. This risk assessment has successfully identified 6 critical information assets, 10 risks in total, and 4 risks that need to be mitigated, followed by proposed mitigation approaches for those risks. Some of the recommendation has been applied by the company and contribute to SLA achievement of the system. The result also showed that application and simulation software provide most prominent risks in FMS service, thus securing these two will eliminate most risk in FMS service.